Relation space, city and education: outlining research possibilities between education and geography - Almeida, Lucilene Ferreira de (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
The research presented articulates the areas of education and geography, based on the analysis of the School Zoning policy, in the city of Rio Branco (AC). We deal with some theoretical background issues, describe the methodology and some research results. We sought to demonstrate the possibility and importance of the relationship between educational indicators such as Ideb (Basic Education Development Index), Seape / AC (State Acre Learning System) and Inse (Socioeconomic Level Index), ICME Material of the School) and Indicator of Adequacy of Teacher Training, with the socio-spatial context of the students, to analyze the results of policies and actions of the State. We show that the urban context in its multiple forms of inequalities, exerts a weight in the educational results.
Keywords: Educação; Geografia; Cidade